Procedures and Properties for a Direct Nano-Micro Integration of Metal and Semiconductor Nanowires on Si Chips - Dawit Gedamu; Ingo Paulowicz; Seid Jebril; Yogendra Kumar Mishra; Rainer Adelung (Journal of Nanotechnology)
1-dimensional metal and semiconductor nanostructures exhibit interesting physical properties, but their integration into modern electronic devices is often a very challenging task. Finding the appropriate supports for nanostructures and nanoscale contacts are highly desired aspects in this regard. In present work we demonstrate the fabrication of 1D nano- and mesostructures between microstructured contacts formed directly on a silicon chip either by a thin film fracture (TFF) approach or by a modified vapor-liquid-solid (MVLS) approach. In principle, both approaches offer the possibilities to integrate these nano-meso structures in wafer-level fabrications. Electrical properties of these nano-micro structures integrated on Si chips and their preliminary applications in the direction of sensors and field effect transistors are also presented.